2019
DOI: 10.1002/stem.3120
|View full text |Cite
|
Sign up to set email alerts
|

KLF2+ stemness maintains human mesenchymal stem cells in bone regeneration

Abstract: Mesenchymal stem cells (MSCs), which are undifferentiated stem cells with the property of stemness and the potential to differentiate into multiple lineages, including osteoblasts, have attracted a great deal of attention in bone tissue engineering. Consistent with the heterogeneity of MSCs, various surface markers have been used. However, it is still unclear which markers of MSCs are best for cell amplification in vitro and later bone regeneration in vivo. Krüppel‐like Factor 2 (KLF2) is an important indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
(110 reference statements)
1
13
0
Order By: Relevance
“…Besides, our results were supported by a previous study whereby WWP1 promoted ubiquitination and degradation of KLF2 [14]. KLF2 has been revealed to play an important role in maintaining the stemness of hMSCs during bone regeneration [24]. Similarly, the silencing of KLF2 has been reported to repress osteoblast differentiation [25].…”
Section: Discussionsupporting
confidence: 88%
“…Besides, our results were supported by a previous study whereby WWP1 promoted ubiquitination and degradation of KLF2 [14]. KLF2 has been revealed to play an important role in maintaining the stemness of hMSCs during bone regeneration [24]. Similarly, the silencing of KLF2 has been reported to repress osteoblast differentiation [25].…”
Section: Discussionsupporting
confidence: 88%
“…A critical requirement in periodontal tissue regeneration is the stemness of a PDLSC-enriched population that retains the features of its original constituent cells. 24 Stemness of PDLSCs is closely related to age, oestrogen levels, hypoxia and the inflammatory microenvironment, strongly limiting their usefulness in tissue engineering. [25][26][27][28] Maintaining stemness of PDLSCs might provide a new strategy for repair of injured periodontal tissue and in situ regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous research efforts have provided evidence for the existence of MSC subpopulations with distinct differentiation propensities, we currently lack the ability to identify and isolate MSCs with high‐self renewal capacity and elevated osteogenic potential. A previous study from the laboratories of Mengfei Yu and Huiming Wang (Zhejiang University, Hangzhou, China) identified the KLF2 transcription factor as an important contributor to the proliferation and pluripotency of MSCs derived from human bone‐marrow, and in their recent STEM CELLS article, the authors report their findings regarding the osteogenic potential of KLF2‐expressing hMSCs . Briefly, Zhou et al investigated a combination of KLF2‐expressing hMSCs and human umbilical vein endothelial cells, given the requirement for an adequate blood supply for optimized tissue regeneration outcomes .…”
Section: Featured Articlesmentioning
confidence: 99%
“…Current hurdles to their widespread implementation include the lack of markers for the isolation of specific MSC subpopulations with elevated osteogenic potential and also the provision of those in vivo conditions, such as the adequate supply of growth factors and an optimized growth matrix, conducive for MSC survival, high levels of osteogenic differentiation, and the repair of critically‐sized defects. In our second Featured Article published this month in STEM CELLS , Zhou et al describe a synergistic interaction between Krüppel‐like factor 2 (KLF2)‐expressing human (h)MSCs and endothelial cells that may significantly influence future bone regeneration and vascular network bioengineering strategies . In a Related Article recently published in STEM CELLS Translational Medicine , Andrews et al compared bone repair techniques and demonstrated the utility of a bone morphogenetic protein 2 (BMP‐2)‐releasing chondroitin sulfate glycosaminoglycan scaffold as a means to support large bone defect healing by engineered MSCs …”
mentioning
confidence: 99%